Perspective taking abilities in amnestic mild cognitive impairment and Alzheimer's disease - Marková, Hana; Laczó, Jan; Andel, Ross; Hort, Jakub; Vlček, Kamil (Behavioural brain research, 2015)
Perspective taking is the ability to imagine what a scene looks like from a different viewpoint, which has been reported to be impaired in Alzheimer's disease (AD). This study compared overhead and first-person view perspective taking abilities in patients with mild cognitive impairment (MCI) and AD. A newly developed Arena Perspective Taking Task (APTT), using an environment of a circular arena, was used to compare 23 AD patients and 38 amnestic MCI patients with 18 healthy controls. The results were contrasted with a published perspective taking test (Standardized Road-Map Test of Direction Sense, RMTDS). The AD group was impaired in both overhead and first-person view APTT versions, but the impairment in the overhead view version applied specifically to women. Patients with aMCI were impaired in the first-person view but not in the overhead view version. Substantial sexual differences were found in the overhead but not in the first-person view APTT version. The RMTDS resembled both APTT versions: patients with aMCI were impaired in this test and also women in both patient groups were less accurate than men. Using the receiver operating characteristic analysis, the highest predictive power for MCI and AD patients diagnosis versus controls was observed for their success rate in the first-person view version. The results suggest distinction between overhead and first-person view perspective taking in the impairment of aMCI patients and the sex differences. The first-person view perspective taking is a potentially important candidate psychological marker for AD.
Keywords: plnění a analýza úkolů; Amnesia; Female; Cognitive Dysfunction; Neuropsychological Tests; ženské pohlaví; průřezové studie; Aging; neuropsychologické testy; lidé; studie případů a kontrol; Aged, 80 and over; kognice; Cross-Sectional Studies; amnézie; Male; Case-Control Studies; Aged; Alzheimer Disease; stárnutí; Task Performance and Analysis; kognitivní dysfunkce; Cognition; Alzheimerova nemoc; senioři nad 80 let; senioři; mužské pohlaví; Humans